Peningkatan Kinerja Guru di SMP Muhammadiyah 1 Purwokerto - Afifah Muzayanah (Jurnal Kependidikan, 2020)
This study aims to describe the improvement of teacher's performance in SMP Muhammadiyah 1 Purwokerto Banyumas Regency, as well as its implications to the quality of education improvement.This research is a qualitative descriptive. This research was conducted in places named SMP Muhammadiyah 1 Purwokerto. The subjects of the study were head of sekolah, vice principal of sekolah, and sekolah teacher. Data collection techniques used observation, interviews, and documentation. Data analysis techniques were interactive models consist of data collection, data reduction, data presentation and conclusions. Test the validity of data was triangulation. The results of this research were a) the improvement of teacher's performance in SMP Muhammadiyah 1 Purwokerto was good and effective. This can be seen from the various efforts or steps that have been done by the educational institutions. The improvement of teacher's performance in SMP Muhammadiyah 1 Purwokerto was done by coaching and developing teacher profession and career, both in the form of education and training, and non-training. Meanwhile, SMP Muhammadiyah 1 Purwokerto conducted several programs and teacher upgrading activities in the form of seminars and workshops, MGMP, seeking new information independently, improving teachers' welfare and educational supervision, b) the improvement of teacher performance in SMP Muhammadiyah 1 Purwokerto has implication on education quality. This was realized with teachers always make learning plans, use varied learning methods and take into account the condition of learners before using certain methods in teaching and learning, and creating a conducive classroom climate. Effective and efficient learning can improve student achievement and the realization of quality education.